An Assessment of the environmental suitability of a potential site for land application of effluents from wastewater treatment facilities in Cebu, Philippines - Atanacio, Almocera T. (Journal of Environmental Science and Management, 2001)
As the demand for domestic and industrial use of water increases, the potential threat to the environment in terms of pollutants from the wastewater may have negative impact on the environment. To a receiving body of water, this can cause undesirable effects such as eutrophication and unpleasant odor. It would be disastrous for the environment of this wastewater were not checked. A good, effective and pro-active wastewater management is important sustainable development in a region such as Cebu. Land application is a potential alternative choice for treating wastewater as a resource rather than a problem to be rectified. The results of the study and regulations on wastewater management in the Philippines. This study hopes to show insights for wastewater treatment plant operators and promote further technical as well as scientific research on land application development.